If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + (3x + 4) = 4 Reorder the terms: 2x + (4 + 3x) = 4 Remove parenthesis around (4 + 3x) 2x + 4 + 3x = 4 Reorder the terms: 4 + 2x + 3x = 4 Combine like terms: 2x + 3x = 5x 4 + 5x = 4 Add '-4' to each side of the equation. 4 + -4 + 5x = 4 + -4 Combine like terms: 4 + -4 = 0 0 + 5x = 4 + -4 5x = 4 + -4 Combine like terms: 4 + -4 = 0 5x = 0 Solving 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '5'. x = 0 Simplifying x = 0
| 92=6+3w | | 92=6+1/2 | | 7x-4=2x+2 | | 92=2+6w | | 0x-.99-3x=-15 | | 92=6+2w | | 2a^2=196 | | 0.4x=8 | | 315=21s | | 15x^2=-3-14x | | 792=-33y | | 24+x^2=10x | | x-2x-1=x+1 | | 0.6+0.3x=0.8+0.4x | | 54+9r-3r^2= | | 54+0r-3r^2= | | 30x-12-3x=-12 | | x^2+5x+11= | | 2w+2(w+20)=380 | | 16z-24=(2z-3) | | 3x-1+x(-3)= | | 3z+14=2x+14 | | .25r+9=10-.75r | | -7x+35=7x-35 | | 0.12x=0.6 | | 225=10(x-65)+75 | | 0.7h=-0.112 | | 5x-7=2x+33 | | f(-3)=x^2+3 | | 2x-5y=-23 | | 1600x=950x+211,250 | | 5x-17=180 |